2022
DOI: 10.3390/v14061154
|View full text |Cite
|
Sign up to set email alerts
|

The Genomic Evolution and the Transmission Dynamics of H6N2 Avian Influenza A Viruses in Southern China

Abstract: In China, the broad prevalence of H6 subtype influenza viruses, increasingly detected in aquatic birds, promotes their exchange materials with other highly pathogenic human-infecting H5N1, H5N6, and H7N9 influenza viruses. Strikingly, some H6 subtype viruses can infect pigs, dogs, and humans, posing risks to public health. In this study, 9 H6N2 viruses recovered from waterfowl species in the Guangdong province of China in 2018 were isolated and sequenced. Phylogenetic analysis revealed that the genome sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Although early literature indicated that H6 AIV has barriers to interspecific transmission, transmission between domestic ducks and terrestrial poultry is uncommon [27]. However, the recent BSSVS procedure by Yuan Z et al showed that ducks were the main source for introducing H6 into chickens and geese [16]. Chickens and geese were also the main poultry infected with H6 AIV, accounting for 16% and 12%, respectively.…”
Section: The Species Distribution Of H6 Subtypementioning
confidence: 99%
See 3 more Smart Citations
“…Although early literature indicated that H6 AIV has barriers to interspecific transmission, transmission between domestic ducks and terrestrial poultry is uncommon [27]. However, the recent BSSVS procedure by Yuan Z et al showed that ducks were the main source for introducing H6 into chickens and geese [16]. Chickens and geese were also the main poultry infected with H6 AIV, accounting for 16% and 12%, respectively.…”
Section: The Species Distribution Of H6 Subtypementioning
confidence: 99%
“…N1, N2, and N6 were the major H6 AIV subtypes in China, with duck derived H6N2 predominating from 2000–2005. After that, N2 and N6 replaced N1 subtypes as the main NA subtypes of H6-subtype AIVs in China, and the proportion of H6N6 subtypes has gradually increased since 2009 [ 13 , 16 ]. In China, the H6 subtype AIV is mainly concentrated in the southern region, with Guangdong Province having the largest number of isolated strains of 608 strains, followed by Hunan Province and Fujian Province.…”
Section: Epidemiological Characteristics Of Avian Influenza Virus H6 ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Group II included H6N2 and H6N6 viruses from the Guangdong and Fujian provinces [ 9 ], whereas viruses in Group III came from Jiangxi, Hunan, and Guangxi and possessed Nas of different subtypes [ 9 ]. In later years, most of the analyzed Chinese H6 viruses belonged to Groups I and II, with an increasing percentage of viruses possessing an NA gene of the N6 subtype [ 10 , 11 , 12 , 13 ]. Moreover, analysis of recent Asian H6 viruses revealed frequent reassortment with other influenza A viruses, resulting in multiple genotypes that have been co-circulating [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%